2004
DOI: 10.1590/s1413-78522004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditivos de infecção em pacientes com fraturas expostas nos membros inferiores

Abstract: 134 pacientes com fraturas expostas dos membros inferiores dos tipos II, IIIA, IIIB e IIIC foram estudados prospectivamente entre fevereiro de 1998 e maio de 2000 no Instituto de Ortopedia e Traumatologia da Faculdade de Medicina da Universidade de São Paulo para determinar os fatores de risco de infecção previsíveis Todos os pacientes foram registrados em um protocolo no qual eles tiveram amostras de fragmentos ósseos iniciais coletadas para cultura bacteriana, avaliação de condições clínica e administração p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
(52 reference statements)
1
11
0
2
Order By: Relevance
“…Some patient and surgical act characteristics can influence the risk of developing SSI (2,(8)(9)(10)(11) . In this study, a statistically significant association was found between the SSI and some variables ( …”
Section: Risk Factors For Ssi In Orthopedic Patientsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some patient and surgical act characteristics can influence the risk of developing SSI (2,(8)(9)(10)(11) . In this study, a statistically significant association was found between the SSI and some variables ( …”
Section: Risk Factors For Ssi In Orthopedic Patientsmentioning
confidence: 99%
“…Other studies involved younger populations, with mean ages of 33 to 35 years (8)(9) . The patient's mean length of preoperative stay was three days and the maximum 361 days.…”
Section: It Should Be Highlighted That Infection Notificationsmentioning
confidence: 99%
See 3 more Smart Citations